2011
DOI: 10.1038/ni.2006
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors Blimp-1 and IRF4 jointly control the differentiation and function of effector regulatory T cells

Abstract: Regulatory T cells (T(reg) cells) are required for peripheral tolerance. Evidence indicates that T(reg) cells can adopt specialized differentiation programs in the periphery that are controlled by transcription factors usually associated with helper T cell differentiation. Here we demonstrate that expression of the transcription factor Blimp-1 defined a population of T(reg) cells that localized mainly to mucosal sites and produced IL-10. Blimp-1 was required for IL-10 production by these cells and for their ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
545
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(595 citation statements)
references
References 62 publications
48
545
1
1
Order By: Relevance
“…Accordingly, IRF4 specifically bound to the IL-21 responsive element and other regulatory regions of the Prdm1 gene. Recently, IRF4 was shown to be crucial in IL-21-induced Blimp-1 expression in B cells and CD4 + T cells (30) as well as in Treg cells (31). Our data extend these observations to CD8 + T cells and suggest the IRF4-Blimp-1 axis as a common regulatory mechanism in lymphocytes.…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, IRF4 specifically bound to the IL-21 responsive element and other regulatory regions of the Prdm1 gene. Recently, IRF4 was shown to be crucial in IL-21-induced Blimp-1 expression in B cells and CD4 + T cells (30) as well as in Treg cells (31). Our data extend these observations to CD8 + T cells and suggest the IRF4-Blimp-1 axis as a common regulatory mechanism in lymphocytes.…”
Section: Discussionsupporting
confidence: 77%
“…When the expression of Treg-associated genes was inspected, we observed a comparably high expression of Ikzf4 (Eos), Ikzf2 (Helios), Nrp1, Il2ra (CD25), and Tnfrsf18 (GITR) in Foxp3 þ RORgt þ T cells and Foxp3 þ Tregs (Figure 2d). In addition, Foxp3 þ RORgt þ T cells displayed a uniquely high expression of genes that were recently associated with Treg populations resident in mucosal tissues, 9,27 including Il10, Gzmb, Prdm1 (Blimp-1), Itgae (CD103), Ctla4, and Icos (Figure 2e). This was in accordance with an activated CD44 int/high CD62L low phenotype, high CD25 surface expression, and increased ICOS levels as determined by fluorescence-activated cell sorting (FACS) analysis in mLNs and colon (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Foxp3 þ RORgt þ T cells showed high expression of Irf4, Prdm1, and Il10. In a recent report, Cretney et al 27 demonstrated that Blimp-1 (encoded by Prdm1) expression was restricted to a population of effector Tregs. Furthermore, they could show that Blimp-1 and IRF4 acted together to induce IL-10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…eT reg were found in LN during allograft responses, indicating that the suppressor function of T reg is mediated by this particular subset during inflammation. eT reg develop from T reg after TCR engagement in the presence of inflammatory cytokines (45). It remains to be tested whether IL-7R signaling promotes eT reg differentiation from cT reg or whether eT reg accumulate in the dLN by proliferation or migration from nonlymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%